2011
DOI: 10.1186/1471-2172-12-61
|View full text |Cite
|
Sign up to set email alerts
|

Immune enhancement by novel vaccine adjuvants in autoimmune-prone NZB/W F1 mice: relative efficacy and safety

Abstract: BackgroundVaccines have profoundly impacted global health although concerns persist about their potential role in autoimmune or other adverse reactions. To address these concerns, vaccine components like immunogens and adjuvants require critical evaluation not only in healthy subjects but also in those genetically averse to vaccine constituents. Evaluation in autoimmune-prone animal models of adjuvants is therefore important in vaccine development. The objective here was to assess the effectiveness of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…31,32 Moreover, the adjuvant (MIM-SIS) used in the ACV studied here is a non-irritating adjuvant that has a very low incidence of AEs, while also being capable of producing a robust immune response against co-administered antigens. 33,34 Based on the reported safety of autologous cancer vaccines among various species, and the properties of MIM-SIS, the low AE rate reported in this population of cats is likely representative of what could be expected with more widespread use.…”
Section: Discussionmentioning
confidence: 89%
“…31,32 Moreover, the adjuvant (MIM-SIS) used in the ACV studied here is a non-irritating adjuvant that has a very low incidence of AEs, while also being capable of producing a robust immune response against co-administered antigens. 33,34 Based on the reported safety of autologous cancer vaccines among various species, and the properties of MIM-SIS, the low AE rate reported in this population of cats is likely representative of what could be expected with more widespread use.…”
Section: Discussionmentioning
confidence: 89%
“…In an earlier study, we have reported the efficiency of SIS in augmenting the immunogenic potential of soluble protein antigens like ovalbumin and keyhole-limpet hemocyanin [18]. We also described that SIS exhibits adjuvanticity without inducing any adverse pathologic inflammatory response even in autoimmune prone NZB/WF1 mice [19]. In this respect, SIS is better than some commercial adjuvants that often induce inflammatory tissue damage at sites of injection.…”
Section: Introductionmentioning
confidence: 94%
“…All adjuvant-treated groups registered high levels of anti-inflammatory cytokines TNFRII, TNFRI, TIMP-1. Interestingly, the Th1 and Th2 responses generated by different adjuvants was directed more toward phthalate as evident by induction of the IgG subclass, whereas the cross reactive anti-ds DNA response was mostly IgM with little IgG subclass switching, indicating no affinity maturation or memory induction, characteristics of T helper activity on antigen-specific B cells (Ghosh and Aachoui, 2011 ).…”
Section: Modes Of Action Of Phytol-derived Adjuvantsmentioning
confidence: 99%